Chytridiomycosis in endemic amphibians of the mountain tops of Córdoba and San Luis: a highly important site for conservation in Argentina - Lescano, Julián Norberto (2013)
Chytridiomycosis is a major threat to amphibian conservation. In Argentina, the pathogenic fungus Batrachochytrium dendrobatidis has been recorded in several localities, and recently, it was registered in amphibians inhabiting low-elevation areas of mountain environ- ments in Córdoba and San Luis provinces. In the present study, we searched for B. dendrobatidis in endemic and non-endemic amphibians on the mountain tops of Córdoba and San Luis provinces. We collected dead amphibians in the upper vegetation belt of the mountains of Cór- doba and San Luis. Using standard histological techniques, the presence of fungal infection was confirmed in 5 species. Three of these species are endemic to the mountain tops of both provinces. Although there are no reported population declines in amphibians in these mountains, the pres- ence of B. dendrobatidis in endemic species highlights the need for long-term monitoring plans in the area